Pelaksanaan Manajemen Organisasi Sosial dalam Meningkatkan Kepemimpinan Efektif Relawan Sikkola Rakyat Indonesia - Rensina Griselda; Tuti Atika (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Social Organization Management is important for running an organization effectively, this must of course be in line with the leadership character of the people in it. To produce effective leadership, management efforts are needed that can improve the quality of human resources in the organization. Management aspects consisting of Planning, Organizing, Actuating, and Controlling are carried out by each management team in the Sikkola Rakyat Indonesia Organization. Volunteers are an important part for a social organization to run properly, so leadership skills are needed for volunteers to be able to carry out the main tasks and functions that already exist, this is of course supported by the management in the organization, the efforts made to improve Effective leadership is expected to produce Self Awareness, Self Regulation, Motivation, Empathy, and Social Skills for the volunteers at Sikkola Rakyat Indonesia. This research aims to find out how social organization management improves the effective leadership of Sikkola Rakyat Indonesia volunteers, and what are the obstacles in the Starban SR Learning House. The method used in this research is a descriptive research method with a qualitative approach. The data collection techniques used were interviews and observation. The results of the research show that the POAC management aspect has an impact on effective leadership for volunteers, but there are obstacles in terms of time, funds and human resources.